2016
DOI: 10.1002/2016jf003819
|View full text |Cite
|
Sign up to set email alerts
|

Measured basal water pressure variability of the western Greenland Ice Sheet: Implications for hydraulic potential

Abstract: The gradient of the hydraulic potential field at the ice‐bedrock interface beneath the Greenland Ice Sheet (GrIS) dictates the routing and energetics of subglacial water, thereby influencing drainage system characteristics and sliding dynamics. In the ablation zone of the GrIS, variable water pressure due to an active subglacial drainage system and basal topography with high relief potentially interact to drive unknown spatial patterns and temporal changes in the hydraulic potential field. Here we present a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
92
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(108 citation statements)
references
References 40 publications
14
92
2
Order By: Relevance
“…Time series of basal water pressure reveal substantial water pressure gradients between adjacent boreholes spaced tens to hundreds of meters apart. While a constant pressure gradient of ~20 kPa m −1 between holes just 20 m apart was observed for more than a month at site 46 km‐11 [ Wright et al ., ], more typically, the magnitude of gradients tended to be transient over periods of many weeks (Figure ).…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…Time series of basal water pressure reveal substantial water pressure gradients between adjacent boreholes spaced tens to hundreds of meters apart. While a constant pressure gradient of ~20 kPa m −1 between holes just 20 m apart was observed for more than a month at site 46 km‐11 [ Wright et al ., ], more typically, the magnitude of gradients tended to be transient over periods of many weeks (Figure ).…”
Section: Resultsmentioning
confidence: 53%
“…Water pressure was measured in boreholes using downhole pressure transducers and was recorded for periods of up to several years [ Wright et al ., ]. Time series of pressure variations and gradients between boreholes yield information about the nature of basal water flow and therefore the nature of the substrate hosting the subglacial drainage system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depressed ice speeds persist through fall and much of winter161415, which is inconsistent with a timescale of hours to days for channel collapse under the thick GrIS ice3616. Additionally, modelling has indicated that gentle surface slopes on the ice sheet should suppress channel formation1617, and low water pressures18 and depressed summer ice speeds19 characteristic of highly efficient channels are only observed near the ice sheet margin. Therefore, in interior regions there may be unrecognized drainage capacity elsewhere in the system.…”
mentioning
confidence: 98%
“…Werder et al, 2013), still fail to reproduce direct borehole observations of subglacial conditions . These include the existence of disconnected areas that show no signs of flow-related changes in water pressure (Hodge, 1979;Engelhardt et al, 1978;Murray and Clarke, 1995;Hoffman et al, 2016), the development of widespread areas of high water pressure during winter Harper et al, 2005;Ryser et al, 2014a;Wright et al, 2016), large pressure gradients over short distances (Murray and Clarke, 1995;Iken and Truffer, 1997;Fudge et al, 2008;Andrews et al, 2014), sudden reorganizations of the drainage system (Gordon et al, 1998;Kavanaugh and Clarke, 2000), high spatial heterogeneity, boreholes exhibiting anti-correlated temporal pressure variations (Murray and Clarke, 1995;Gordon et al, 1998;Andrews et al, 2014;Lefeuvre et al, 2015;Ryser et al, 2014a), and englacial conduits (Fountain and Walder, 1998;Nienow et al, 1998b;Gordon et al, 1998;Fountain et al, 2005;Harper et al, 2010).…”
Section: Introductionmentioning
confidence: 99%